2019
DOI: 10.1021/acs.biochem.9b00732
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Independent Kinetic Isotope Effects as Evidence for a Marcus-like Model of Hydride Tunneling in Phosphite Dehydrogenase

Abstract: Phosphite dehydrogenase catalyzes the transfer of a hydride from phosphite to NAD+, producing phosphate and NADH. We have evaluated the role of hydride tunneling in a thermostable variant of this enzyme (17X-PTDH) by measuring the temperature dependence of the primary 2H kinetic isotope effects (KIEs) between 5 and 45 °C. Pre-steady-state kinetic measurements were used to demonstrate that the hydride transfer is rate-determining across this temperature range and that the observed KIEs are equal to the intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Nevertheless, the V203A substitution might allow the nicotinamide ring to fluctuate and affect the puckering during catalysis, which could be reflected in the diminished hydrogen tunneling, but the geometry of the ring and the temperature factors are very similar to those in the other enzymes (Tables and ). However, a new water molecule is hydrogen bonded to the guanidinium NH2 of Arg-369 and the phosphate O1N of NAD and also interacts with C6N of the nicotinamide ring. , Oxygens of highly conserved residues interact with the nicotinamide ring, Val-292 O to C2N and Thr-178 OG2 to C4N, in the ADH structures reported here and might also affect the chemistry of the nicotinamide ring. , It is interesting that the substitution of the homologous threonine (Thr-104) in phosphite dehydrogenase affects catalysis and hydrogen tunneling …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, the V203A substitution might allow the nicotinamide ring to fluctuate and affect the puckering during catalysis, which could be reflected in the diminished hydrogen tunneling, but the geometry of the ring and the temperature factors are very similar to those in the other enzymes (Tables and ). However, a new water molecule is hydrogen bonded to the guanidinium NH2 of Arg-369 and the phosphate O1N of NAD and also interacts with C6N of the nicotinamide ring. , Oxygens of highly conserved residues interact with the nicotinamide ring, Val-292 O to C2N and Thr-178 OG2 to C4N, in the ADH structures reported here and might also affect the chemistry of the nicotinamide ring. , It is interesting that the substitution of the homologous threonine (Thr-104) in phosphite dehydrogenase affects catalysis and hydrogen tunneling …”
Section: Discussionmentioning
confidence: 78%
“…3,70 It is interesting that the substitution of the homologous threonine (Thr-104) in phosphite dehydrogenase affects catalysis and hydrogen tunneling. 71 Dynamics of Catalysis. According to models that explain the energetics of enzyme catalysis (described in textbooks), enzymes use the energy gained from substrate binding to orient the reactants, destabilize the ground state, and stabilize the transition state.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In the past two decades, however, it has been frequently observed that KIEs (both small and large) are temperature independent (Δ E a ≈ 0) in the wild-type enzymes ( wt -enzymes) around physiological temperature conditions, but they become temperature dependent to various extents with enzyme variants (Δ E a > 0 or even above the semiclassical limit). A few contemporary H-tunneling theories have been established or used to explain the unusually small Δ E a and its change relating to enzyme structures and further to attempt to provide information for the possible role of protein thermal motions in catalysis. ,, One largely used is the vibration-assisted activated H-tunneling (VA-AHT) model, which could include the Marcus-like model and TS theory extension, both of which involve a full H-tunneling process. ,, These phenomenological models presume that heavy atom motions bring H-donor and -acceptor to a tunneling-ready-state (TRS) where the activated reactant and product moieties have matching energy, allowing H-tunneling to occur over a range of donor–acceptor distances (DADs) sampled by the constructive heavy atom vibrations. Within that model, KIE is a function of DAD TRS , and its temperature dependence is related to the density of DAD TRS distributions. , Therefore, the Δ E a ≈ 0 with wt -enzymes has been explained in terms of the well-organized reaction coordinate in which DAD TRS is short and the range of DAD TRS ’s sampled is narrow.…”
mentioning
confidence: 99%
“…These calculations neglect the effects of hydrogen tunneling, which was implicated by a recent analysis of the temperature dependence of the primary hydrogen/deuterium (H/D) kinetic isotope effects (KIEs) for this enzymatic reaction. 46 In this previous work, the experimental H/D KIE was found to increase from 2.23 to 2.30 as the temperature was increased from 5 to 45 °C. The theoretical analysis of such effects is challenging given the complexity of the system, the small temperature range studied, and the small change in the KIE with temperature.…”
Section: ■ Methodsmentioning
confidence: 80%
“…These calculations neglect the effects of hydrogen tunneling, which was implicated by a recent analysis of the temperature dependence of the primary hydrogen/deuterium (H/D) kinetic isotope effects (KIEs) for this enzymatic reaction . In this previous work, the experimental H/D KIE was found to increase from 2.23 to 2.30 as the temperature was increased from 5 to 45 °C.…”
Section: Methodsmentioning
confidence: 95%